«MATLA AL-SADAYN WA-MAJMA AL-BAHRAYN» OF ABDURAZZAK SAMARKANDI AS A VALUABLE SOURCE ON THE DESCRIPTION OF CULTURAL AND EDUCATIONAL PROCESSES OF THE TEMURID PERIOD (Scientific journal of the Fergana State University, 2023)
Abdurazzaq Samarkandi's “Matlai Sadаin wa Majmai Bahrain”, which is a valuable source for studying the events of the Timurid period, provides profound information in many areas. In the source, in addition to the activities of the Timurids in the political, social and military spheres, we can also obtain information about the cultural and educational processes. The article discusses exactly what information we can get about the spiritual-enlightenment processes.